(untitled) (Research, Society and Development, 2022)
Holistic nursing has progressed in its work directly when applying complementary therapies, in view of the benefits that can be brought to the population, such as acupuncture, a multiprofessional and ethical technique. The present review study sought to evaluate advances in the clinical use of acupuncture as a possibility for the field of nursing and health, documented through clinical and randomized studies. This is an integrative review research carried out through an advanced search in the PubMed database, taking into account the following inclusion criteria: clinical trials and controlled and randomized trials; articles published in the last year; that had a full text available, in Portuguese, English or Spanish and that addressed advances in the use of acupuncture for nursing and the health area. Duplicate articles in the database and those that did not address the topic under study were excluded. It was found that auricular electroacupuncture was effective in improving symptoms in patients with Diabetes Mellitus, and that it also offers a quality of life in patients with stable angina. In addition, acupuncture with low-level laser stimulation gradually reduced the intensity of postoperative pain in patients undergoing total knee arthroplasty; invasive laser acupuncture significantly reduced pain in patients with chronic low back pain; it also proved to be viable for the treatment of chronic pain in adults with sickle cell disease and, through the intradermal needle technique, postoperative pain relief was obtained.